MENERAPKAN POLA ASUH KONSISTEN PADA ANAK AUTIS - Rina Mirza (JURNAL TARBIYAH, 2016)
The term of autism on the rise lately, the population of autistic children are increasingly growing, so it requires us to be more familiar with autism closer. Besides providing the right training or therapy for changes in behavior, implementation of consistent parenting is also one of the efforts to be made by parents on children with autism. The purpose of this paper is to provide an understanding of the society in general and parents of children with autism in particular regarding the various theories relating to autism, behavioral therapy can be administered to children with autism and the implementation of appropriate parenting to assist children with autism.Keywords: autism, therapy, consistent parenting